Early diagnosis of occult pulmonary embolism secondary to lower limb fractures: summary of 18 cases - Di, Luqin; Chen, Zheng; Wang, Xiaoyan; Zhang, Jiao; Zhang, Jing; Ding, Junqin (Frontiers in Medicine, 2024)
Objectives Pulmonary thromboembolism is a severe but probably underdiagnosed disorder. Patients with lower limb fractures are at high risk for pulmonary thromboembolism. This study aimed to demonstrate the early identification strategies for occult pulmonary thromboembolism. Methods From January to December 2022, 18 patients diagnosed with pulmonary thromboembolism were reviewed for this study. Data on patients’ demographics, laboratory test results, and radiographic findings were collected. Finally, the data was analyzed. Results Eighteen patients with lower limb fractures were included in this study. All of them present different symptoms, including 12 cases (12/18, 66%) of unexplained decrease in oxygen saturation; 16 patients had deep vein thrombosis in the lower limbs, with nine cases involving proximal veins and seven involving distal veins. One patient had an antithrombin III level of 35%. Thirteen cases were diagnosed with pulmonary embolism using CT pulmonary angiography. Four patients had pulmonary embolisms incidentally detected during coronary CT angiography, and one patient during aortic CT angiography. Conclusion Patients with lower limb fractures showing chest tightness and unexplained decrease in finger pulse oxygen levels should be assessed for pulmonary thromboembolism. Simultaneously, selecting appropriate diagnostic tools is essential to guaranteeing quick and accurate diagnosis.